Different expression of MIB1 in primary site of non-Hodgkin lymphoma and its bone marrow deposits, a pilot study - Malysz J; Evans JJ; Acon-Laws M; Bayerl MG; Creer MH (Dove Medical Press, 2017)
Jozef Malysz,1 Juanita J Evans,2 Malcolm Acon-Laws,3 Michael G Bayerl,1 Michael H Creer1 1Department of Pathology, Penn State Milton S Hershey Medical Center, Hershey, PA, 2Department of Pathology, St. John Heath – Providence, Southfield, MI, USA; 3Laboratorio de Patologia Hospital Cima, San Jose, Costa Rica Abstract: Evaluation of mindbomb E3 ubiquitin protein ligase 1 (MIB1) (Ki67) proliferation index (PI) in B-cell non-Hodgkin lymphomas is increasingly a common addition to classification of lymphoma and staging procedures. Clinicians relay on PI as a surrogate marker of biologic activity; however, no established guidelines have been published whether PI at the primary site of the tumor gives the same answer as evaluation of tumor in staging marrow. In our study, dual immunohistochemical staining for MIB1 and CD20 was performed on tissue from primary site and bone marrow involved by B-cell non-Hodgkin lymphoma to compare PI for each individual patient. For all patients, MIB1 expression was higher at primary tumor site as compared to staging marrow. Additional analysis was performed to investigate the degree of difference depending on lymphoma morphology. Patients with large cell lymphoma at the primary site and large cell morphology in the marrow (LCL-L), those with large cell morphology at the primary site and small cell morphology in the marrow (LCL-S), and those with small cell morphology at the primary site and small cells in the marrow (SCL-S) were compared. As expected, LCL cases had a higher mean PI at the primary site when compared to SCL cases (28.5% vs 2.8%, P=0.0001). In addition, the most significant difference between medullary and extramedullary PI was observed in cases with discordant morphology (LCL-S) (21% vs 1.1%, P=0.009). Our results indicate that PI of lymphoma within the bone marrow should not be used as a surrogate prognostic indicator of lymphoma biology in its primary site. Keywords: proliferation index, biologic behavior, prognosis